Tanshinone IIA changed the amniotic fluid volume and regulated expression of AQP1 and AQP3 in amniotic epithelium cells: a promising drug treating abnormal amniotic fluid volume - Shuangjia Pan; Yehui Lan; Baoyi Chen; Yujia Zhou; Xinxin Ying; Ying Hua (BMC, 2023)
Abstract Background Many studies have confirmed the association of aquaporins (AQPs) with abnormal amniotic fluid volume (AFV). In our previous experiments, we found that Tanshinone IIA was able to regulate the expression of AQP1 and AQP3. However, the exact mechanism by which Tanshinone IIA regulates AQPs protein expression and its effect on AFV remains unclear. The purpose of this study was to investigate the effects of Tanshinone IIA on AFV and the possible molecular mechanism of regulation of AQP1 and AQP3. Methods The expression of AQPs protein in the amniotic membranes was compared between pregnant women with normal pregnancy and those with isolated oligohydramnios. The AQP1 knockout (AQP1-KO) mice and wild-type (WT) mice were treated with saline or Tanshinone IIA (10 mg/kg) at 13.5GD and 16.5GD. Human amniotic epithelium cells (hAECs) from pregnant women with normal AFV and isolated oligohydramnios were incubated with 35 μmmol/L Tanshinone IIA or 25 mmol/L LiCl [inhibitor of glycogen synthetic kinase 3β (GSK-3β)]. The protein expressions of AQPs, GSK-3β, phospho-GSK-3β (Ser9) in fetal membranes of mice and human amniotic epithelium cells were detected by western blotting. Results The expression of AQP1 protein in the amniotic membrane of isolated oligohydramnios was increased compared with normal pregnancy. The AFV in AQP1-KO mice is higher than that in WT mice. In wild-type mice, AFV in Tanshinone IIA group was significantly higher than that in control group, and AQP1 protein expression was significantly lower than that in control group, but in AQP1 knockout mice, Tanshinone IIA reduced amniotic fluid volume and AQP3 protein expression at 16.5GD. Tanshinone IIA reduced AQP1, AQP3 and p-GSK-3β (Ser9) protein expression in normal hAECs, and this effect was inhibited by LiCl. In hAECs with oligohydramnios, the down-regulation of AQP1 and up-regulation of AQP3 by Tanshinone IIA was independent of GSK-3β signaling pathway. Conclusions Tanshinone IIA may increase AFV in normal pregnancy by downregulating AQP1 protein expression in the fetal membranes, which may be associated with p-GSK-3β signaling pathway. But a larger AFV in AQP1-KO mice was significantly attenuated by Tanshinone IIA, which may be related to AQP3. Tanshinone IIA is a promising drug for the treatment of amniotic fluid abnormality.